The NLRP3 Inflammasome Mediates in vivo Innate Immunity to Influenza A Virus through Recognition of Viral RNA - Allen, Irving C. (2009)
NLR genes mediate host immunity to various pathogenic stimuli. However, in vivo evidence for NLR involvement in viral sensing has not been widely investigated and remains controversial. As an ultimate test of the physiologic role of NLRP3 during RNA viral infection, this work explores the in vivo role of NLRP3 inflammasome components during influenza virus infection. Mice lacking Nlrp3, ASC, or Caspase-1, but not Nlrc4, exhibit dramatically increased mortality but reduced immune response following influenza virus exposure. Utilizing analogs of dsRNA (poly(I:C)) and ssRNA (ssRNA40), we demonstrate that NLRP3-mediated response can be activated by RNA species. Mechanistically, NLRP3 inflammasome activation by influenza virus is dependent upon lysosomal maturation and reactive oxygen species. Inhibition of ROS induction eliminated IL-1β production in animals during influenza infection. Together, these data place the NLRP3 inflammasome as an essential component in host defense against influenza infection through the sensing of viral RNA.